Back Cover: Nanoparticles as contrast agents for photoacoustic brain imaging. Issue 1 (12th March 2021) - Liu, Xingang; Duan, Yukun; Liu, Bin
Abstract : Photoacoustic imaging has emerged as a promising technique for real‐time detection and diagnosis of brain‐related pathologies. In article number 2021, 2, 4‐19, the author herein provides an overview of the latest developments of aggregated nanoparticles as high‐performance PA contrast agents specifically designed for photoacoustic imaging of brain tumors, brain vascular, and other brain‐related diseases. (DOI: 10.1002/agt2.26 )